KOMPARASI PENERAPAN BAHASA JURNALISTIK PORTAL BERITA DARING NASIONAL - kartini rosmalah dewi katili (President University, 2019)
Online media in the form of news portals always presents the latest news and is easily accessible when and where to keep abreast of the times. However, the language of the news that is applied in the online news portal is often not in accordance with the rules of the journalistic language that applies. The purpose of this study is to find out how comparisons of journalistic languages are applied to national online news portals, namely Antaranews.com and Kompas.com. This study uses the theory of the concept of Spelling and Indonesian Journal which is owned by Haris Sumadiria. The method used is kuanlitatif approach with content and description analysis. The results of the study found that the comparison of journalistic language applications between Antaranews.com was 51% while Kompas.com was 49%. Based on the results of this study, there are many indicators that are not found in both media, namely simple, concise, solid, straightforward, clear and clear. This comparison occurs because each media has the writing rules of each guide or white book. For further research to be more maximal in looking for more and wider references.